Dupuytren's Disease: An Outcomes-Focused Update - Almadani, Yasser H.; Vorstenbosch, Joshua; Efanov, Johnny Ionut; Xu, Liqin (Seminars in Plastic Surgery, 2021)
Dupuytren's disease (DD) remains a common fibroproliferative condition with significant sequelae and impact on patient's lives. The etiology of DD is poorly understood, and genetic predisposition is thought to be a strongly associated factor. Despite remarkable strides in improving our molecular understanding of DD, clinical treatment options have not yet overcome the frequently encountered challenge of recurrence. Recurrence rates continue to shape the prognosis of this fibrotic condition. In this outcomes-focused article, the various treatment modalities are reviewed. This further emphasizes the importance of patient education and providing them with the information to make informed decisions about their treatment.
Keywords: Dupuytren's disease; collagenase injection; needle aponeurotomy; open fasciectomy